Prevalence of Angular Bone Defects in Chronic Periodontitis Patients with and without Systemic Diseases - Niveda Rajeshwaran1 , Arvina Rajasekar2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of the current study was to assess the distribution of angular defects in both maxillary and mandibulararches in chronic periodontitis patients with and without systemic diseases. This retrospective study wasconducted among 200 patients who reported to Saveetha Dental College and Hospitals, Chennai from June2019 to March 2020. A total of 200 chronic periodontitis patients were enrolled and assessed for numberof angular bone defects using panoramic radiographs. The study participants were divided into two groups.Group 1 (n=100, 50 males and 50 females): chronic periodontitis patients with systemic diseases; Group 2(n=100, 50 males and 50 females): chronic periodontitis patients without systemic diseases. Data regardingthe number of angular defects of the study population were collected and analysed. Among 100 systemicallyhealthy patients, 102 sites presented with angular defects. Among 100 systemically diseased patients, 320sites presented with angular defects. In gender wise comparison, the number of angular defects were higherin females as compared to males. When the distribution of angular bone defects were compared betweenmaxillary and mandibular arches, angular bone defects were predominantly observed in mandibular arch.Therefore, this study showed higher prevalence of angular bone defects in chronic periodontitis patientswith systemic diseases (320 sites) as compared to the ones without systemic diseases (102 sites).